Fund Transactions and Reserve Creation - Fawzi, Samir (IMF Working Papers; Working Paper ;, 1992)
This paper describes the effects of Fund transactions on members' external reserves, estimates the net reserve creation or absorption by the Fund in the 1980s, and compares the role of the Fund in this respect with that of other sources of international reserves.